Di-π-Methan-Umlagerungen von methylsubstituierten Allylbenzolen - Jean-Pierre Fasel; Hans-Jürgen Hansen (CHIMIA)
Allylbenzene (3) and its derivatives bearing methyl groups at the aromatic ring or at C(1') of the allyl chain (see scheme 1-3, and 6) can cleanly be transformed into the corresponding cyclopropylbenzenes via a triplet di-π-methane rearrangement when irradiated with a mercury high pressure lamp through a filter of Jena glass in acetonitrile/acetone solution. Under the same conditions 2'-butenyl-3,5-dimethylbenzene (15) shows only a rapid trans,cis isomerization. Also no di-π-methane rearrangement is observed when (2'-methylallyl)-3,5-dimethylbenzene is irradiated in acetonitrile/acetone solution. Irradiations of the allylbenzenes in benzene solution using a quartz filter give as a rule complex reaction mixtures due to subsequent photoreactions of the primarily formed cyclopropylbenzenes (see scheme 4-6).